Pengaruh Celebrity Endorser, Brand Image, dan Customer Experience Terhadap Repurchase Intention pada Produk Mie Instan Lemonilo: Studi pada Masyarakat Kota Surabaya - Ria Mei Yustiana; Lia Nirawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of Celebrity Endorser, Brand Image, and Customer Experience on Repurchase Intention. This research uses a quantitative approach with an associative type of research. The population in this study were consumers of Lemonilo instant noodle products in the city of Surabaya. In this research, questionnaires were used to collect data. The sample in this study was 100 respondents using non-probability sampling and purposive sampling techniques, with the criteria being that consumers of Lemonilo instant noodle products in the city of Surabaya were at least 15 years old and had purchased and consumed Lemonilo instant noodles at least twice. Data analysis in this research includes testing validity, reliability, classical assumptions, multiple linear regression, and hypothesis testing and all analysis processes are carried out using the SPSS 26 program. The results of this research show that it is simultaneously proven by Fcount 53.908 > Ftable 2.700 and the value sig 0.000 so that Celebrity Endorser, Brand Image and Customer Experience have a significant effect on Repurchase Intention. Furthermore, it is partially proven by tcount 2.959 > ttable 1.985 and a sig value of 0.004 so that Celebrity Endorser has a significant effect on Repurchase Intention for Lemonilo instant noodle products in the city of Surabaya. It is partially proven by tcount 4.210 > ttable 1.985 and a sig value of 0.000 so that Brand Image has a significant effect on Repurchase Intention for Lemonilo instant noodle products in the city of Surabaya. It is partially proven by tcount 8.445 > ttable 1.985 and a sig value of 0.000 so that Customer Experience has a significant effect on Repurchase Intention for Lemonilo instant noodle products in the city of Surabaya.